Rola controllera w zarządzaniu ryzykiem w koncernie międzynarodowym - Dyczkowska, Joanna (The role of a controller in risk management within a multinational company, 2006)
Integration of global economies, growing complexity of a business environment, dynamic development of organisations and competition challenge entrepreneurs to guarantee a safety future of their businesses. The paper focuses on a role of controller in a process of risk management. The competence of a controller comprises not only obligations set by the law but also those required to make risk management process work correctly. The article emphasizes the importance of a phase of identification of risks in a multinational company as a prerequisite for successful completion of other stages of the process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 87-96